Approaches to the choice of tools for adaptive learning based on highlighted selection criteria - Yaroslava B. Sikora; Olena Yu. Usata; Oleksandr O. Mosiiuk; Dmytrii S. Verbivskyi; Ekaterina O. Shmeltser (Academy of Cognitive and Natural Sciences, 2021)
The article substantiates the relevance of adaptive learning of students in the modern information society, reveals the essence of such concepts as "adaptability" and "adaptive learning system". It is determined that a necessary condition for adaptive education is the criterion of an adaptive learning environment that provides opportunities for advanced education, development of key competencies, formation of a flexible personality that is able to respond to different changes, effectively solve different problems and achieve results. The authors focus on the technical aspect of adaptive learning. Different classifications of adaptability are analyzed. The approach to the choice of adaptive learning tools based on the characteristics of the product quality model stated by the standard ISO / IEC 25010 is described. The following criteria for the selecting adaptive learning tools are functional compliance, compatibility, practicality, and support. By means of expert assessment method there were identified and selected the most important tools of adaptive learning, namely: Acrobatiq, Fishtree, Knewton (now Wiley), Lumen, Realize it, Smart Sparrow (now Pearson). Comparative tables for each of the selected tools of adaptive learning according to the indicators of certain criteria are given.